Color evaluation of a resin cement light polymerized by different light sources and submitted to potentially staining beverages - Tatiane Cristina DOTTA; Vinicius Cappo BIANCO; Alma Blásida Concepción Elizaur Benitez CATIRSE; Mayara Manfrin ARNEZ; Raisa CASTELO; Ana Paula Terossi de GODOI
Abstract Introduction The color stability of resin cements, whether dual-pre-cured or photopolymerizable, as well as the color of the dental substrate, are fundamental for the aesthetic success of ceramic restorations, since the ceramic presents a high level of translucency due to its small thickness. Objective The aim of this in vitro study was to evaluate the color of a resin cement light polymerized by different light sources and immersed in potentially staining beverages. Material and method Were made 42 specimens of resin cement Variolink-Esthetic (2×6mm) (n=7), being half polymerized with LED light (F1) and half with Halogen light (F2). The specimens were stored in artificial saliva at 37 °C±1 °C. After 24 hours, they were polished with abrasive discs, and divided for the purpose of being submitted to the different solutions for 2 minutes per day, for 28 days, as follows: S1 - Coca-Cola; S2 - Red Wine; and S3 - Distilled Water (Control). Five color readouts were taken: T0 - initial; T1 - 7 days; T2 - 14 days; T3 - 21 days; and T4 - 28 days; with a spectrophotometer (Model SP62S). The color change data (ΔE*) were submitted to statistical analysis, ANOVA and Tukey (p≤0.05). Result Analyzing the factor solution, S2 (5.89 (±0.02)), produced a higher ΔE* value than S1 (3.79 (±0.02)) and (S1), a higher value than S3 (1.41 (±0.02)). Analyzing the factor light source, F2 (4.05 (±0.12)), produced a higher ΔE* value than F1 (3.33 (±0.12)). When analyzing the factor time, ΔE* values were found to increase gradually over the course of time: T1(2.36 (±0.08)); T2(3.27 (±0.08)); T3(4.06 (±0.08)); and T4(5.09 (±0.08)). Conclusion It was concluded that red wine produced a greater color change; Halogen light promoted highest degree of pigmentation; and the longer the time of immersion, the greater the color change of the material.